2008
DOI: 10.1016/j.neuroscience.2007.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Urocortin 1 microinjection into the mouse lateral septum regulates the acquisition and expression of alcohol consumption

Abstract: Previous studies using genetic and lesion approaches have shown that the neuropeptide Urocortin 1 (Ucn1) is involved in regulating alcohol consumption. Ucn1 is a corticotropin releasing factor (CRF)-like peptide that binds CRF1 and CRF2 receptors. Perioculomotor urocortin-containing neurons (pIIIu), also known as the non-preganglionic Edinger-Westphal nucleus, are the major source of Ucn1 in the brain and are known to innervate the lateral septum. Thus, the present study tested whether Ucn1 could regulate alco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 78 publications
(70 reference statements)
5
54
1
Order By: Relevance
“…A similar effect is seen when a CRF-1 receptor antagonist is administered to normal mice , and, as noted above, an antagonist also attenuates ethanol DID (Sparta et al 2008). Also as noted above, intra-septal CRF and urocortin 1 both reduce DID (Ryabinin et al 2008). Ethanol intake can also be potentiated following induction of physical dependence ( Lopez & Becker 2005), and these increases are also blocked by CRF 1 antagonists (Chu et al 2007;Finn et al 2007;Richardson et al 2008) or are absent in the knockout (Chu et al 2007).…”
Section: Discussionsupporting
confidence: 57%
“…A similar effect is seen when a CRF-1 receptor antagonist is administered to normal mice , and, as noted above, an antagonist also attenuates ethanol DID (Sparta et al 2008). Also as noted above, intra-septal CRF and urocortin 1 both reduce DID (Ryabinin et al 2008). Ethanol intake can also be potentiated following induction of physical dependence ( Lopez & Becker 2005), and these increases are also blocked by CRF 1 antagonists (Chu et al 2007;Finn et al 2007;Richardson et al 2008) or are absent in the knockout (Chu et al 2007).…”
Section: Discussionsupporting
confidence: 57%
“…The authors used a limited access procedure, which takes advantage of higher levels of activity, fluid and alcohol consumption that are observed in mice during early hours into the dark portion of the circadian cycle. Injection of Ucn1 into the LS of C57 mice significantly attenuated ethanol consumption both in the expression phase of ethanol drinking and during the acquisition phase of alcohol consumption [134].…”
Section: Corticotropin-releasing Factor (Crf) and Crf-like Peptidesmentioning
confidence: 88%
“…The hypothalamus is a long-proposed integrator of consummatory responses, but hypothalamic subregions affected by ethanol have not been mapped in sufficient detail [133]. A recent study by Ryabinin et al [134] confirmed the importance of Ucn1 innervation and in particular of the LS in the regulation of alcohol consumption. In a series of experiments the authors injected Ucn1 or CRF bilaterally at various doses into the lateral septum of male C57BL/6J mice and immediately after the injection tested ethanol consumption.…”
Section: Corticotropin-releasing Factor (Crf) and Crf-like Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…71 Regions of the extended amygdala as well as the lateral septum appear to mediate CRF involvement in alcohol intake. 67,72 Alcohol consumption is also attenuated in CRF 1 knockout mice when compared to that of littermate controls. 73 These findings suggest that alcohol dependence engages the brain's stress systems by either altering CRF release or up-regulating CRF 1 receptors in limbic regions such as the amygdala.…”
Section: ■ Neurochemical Alterations In Alcoholismmentioning
confidence: 99%